Strategies to fight disinformation in health: Is it possible for a brazilian podcast to reach any target audience? - Silva, Iorana Candido da; Nogueira, Maria Rayssa do Nascimento; Oliveira, Carlos Henrique de; Santos, Marcos Nascimento dos; Santos, Vania dos; Nicolete, Larissa Deadame de Figueiredo (Seven Editora, 2023)
Aim: Knowing the use in the education of podcasts was occurring in some countries, the present work developed one in Portuguese. The aim was to promote health and combat disinformation in Brazil. Methods: Different categories of Podcasts were created: shorter/longer; with/without guests and disease-related issues or other topics about prevention/health education. After that, the audios were edited and submitted on platforms: Results: It was analyzed through the data generated by the published episodes. It was observed that duration vs several reproductions did not correlate with (p=0.2521). Then, the presence/absence of guests (p=0.1779). However, themes related to infectious and chronic diseases obtained more significant results (p=0.0466) when compared to the other topics. Also, we noticed that our listeners are primarily men aged between 18 and 27 years old and residing in Brazil. Conclusion: Podcasts may be able to disseminate knowledge, however, themes and the type of audience must be considered to choose this kind of approach. DOI:https://doi.org/10.56238/ptoketheeducati-029